Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1038/s41467-022-34017-x
|View full text |Cite|
|
Sign up to set email alerts
|

Cryo-EM structures of thermostabilized prestin provide mechanistic insights underlying outer hair cell electromotility

Abstract: Outer hair cell elecromotility, driven by prestin, is essential for mammalian cochlear amplification. Here, we report the cryo-EM structures of thermostabilized prestin (PresTS), complexed with chloride, sulfate, or salicylate at 3.52-3.63 Å resolutions. The central positively-charged cavity allows flexible binding of various anion species, which likely accounts for the known distinct modulations of nonlinear capacitance (NLC) by different anions. Comparisons of these PresTS structures with recent prestin stru… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 89 publications
2
24
0
Order By: Relevance
“…The presumable location of a bound chloride ion is resolved in the structure of SLC26A6 at a low contour of the map (Figure 4B, Figure 2-figure supplement 2B). This position concurs with positions inferred from known structures of paralogs, which show binding of Cl - and HCO 3 to an equivalent location (Chi et al, 2020; Futamata et al, 2022; Ge et al, 2021; Liu et al, 2022) (Figure 4B, Figure 4-figure supplement 1). The anion binding site is placed between the opposed short helices α3 and α10, which partly span the membrane and whose N-termini are aligned to face each other in the center of the core domain (Figure 4A).…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…The presumable location of a bound chloride ion is resolved in the structure of SLC26A6 at a low contour of the map (Figure 4B, Figure 2-figure supplement 2B). This position concurs with positions inferred from known structures of paralogs, which show binding of Cl - and HCO 3 to an equivalent location (Chi et al, 2020; Futamata et al, 2022; Ge et al, 2021; Liu et al, 2022) (Figure 4B, Figure 4-figure supplement 1). The anion binding site is placed between the opposed short helices α3 and α10, which partly span the membrane and whose N-termini are aligned to face each other in the center of the core domain (Figure 4A).…”
Section: Resultssupporting
confidence: 85%
“…The presumable location of a bound chloride ion is resolved in the structure of SLC26A6 at a low contour of the map (Figure 4B, Figure 2-figure supplement 2B). This position concurs with positions inferred from known structures of paralogs, which show binding of Cland HCO3to an equivalent location (Chi et al, 2020;Futamata et al, 2022;Ge et al, 2021;Liu et al, 2022) (Figure 4B, Figure 4-figure supplement 1).…”
Section: The Transmembrane Domainsupporting
confidence: 85%
See 2 more Smart Citations
“…A recent cryo-EM study on mouse pendrin (Liu et al, 2023) revealed a homodimeric architecture that is similar to prestin (Bavi et al, 2021; Butan et al, 2022; Futamata et al, 2022; Ge et al, 2021) and other SLC26 proteins (Chi et al, 2020; Tippett et al, 2023; Walter et al, 2019). The transmembrane domain consists of the gate and the core domains, and the ion translocation pathway is located in between them ( Fig.…”
Section: Resultsmentioning
confidence: 99%